Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes - Bota-Sierra, Cornelio Andrés; Sandoval-H, Juliana; Palacino-Rodríguez, Fredy (Zootaxa, 2019)
Andaeschna is a small and poorly known genus of dragonflies that inhabits the Andes, from Venezuela to northwestern Argentina. Here we describe Andaeschna occidentalis sp. nov., first species of the genus recorded in the Western Andes, specifically from the Tatamá National Park in Colombia. Males of this species can be differentiated from the other four species in the genus by the unique shape of the distal segment of the vesica spermalis. Likewise, females can be distinguished by their smaller and broader cerci (slightly shorter than S9) and its subquadrate point. The discovery of this beautiful species expands the range of the genus, previously known only in the Eastern Andes.